PEMANFAATAN SISTEM INFORMASI PENANGGULANGAN KRISIS KESEHATAN TERHADAP KESIAPSIAGAAN DINAS KESEHATAN KOTA PALU DALAM PENANGGULANGAN BENCANA - Lepsy Saputri; Arif Rianto Budi Nugroho; Purbudi Wahyuni (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
The 2018 earthquake disaster in Palu City caused chaos in health services due to an unclear information system, lack of preparedness, and limited knowledge of disaster and health crisis management—including disaster information, resource data, manpower, funding, infrastructure, task division, communication flow, and alternative planning. This study aims to analyze the use of a health crisis management information system to support preparedness at the Palu City Health Office. A mixed-methods approach was used, combining quantitative and qualitative methods through questionnaires, interviews, and observations. The study involved 55 respondents and 3 informants within the Palu City Health Office’s work area. The results show that in terms of preparedness: knowledge and attitude fall into the “ready” category; emergency response plans and early warning systems are in the “unprepared” category; and resource mobilization is in the “almost ready” category. Furthermore, the health crisis information system—across pre-crisis, during-crisis, and post-crisis phases—has not been effectively used or integrated into disaster preparedness efforts.